(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Micropropagation of fruit crops is essential for producing disease free plants, ensuring rapid multiplication, and preserving the genetic integrity of the original plant materials. Musa paradisiaca, a widely cultivated fruit crop in Bangladesh is commonly propagated on a large-scale using sucker explants. An efficient in vitro micropropagation protocol was developed using healthy suckers of Musa paradisiaca cultured on MS medium supplemented with 4.0 mg/l BAP, 0.5 mg/l IAA and 20 mg/l adenine sulphate, this combination resulted in the formation of highly proliferative multiple shoots. For shoot elongation, MS medium containing 4.0 mg/l BAP, 0.5 mg/l IAA, and 13% coconut water produced the greatest average shoot length of 8.4 cm. Rooting was most successful on half-strength MS medium supplemented with 1.0 mg/l IBA. The regenerated plantlets were successfully acclimatized and established in field conditions, achieving a 100% survival rate. These findings demonstrate an optimized protocol for the large-scale production of genetically uniform and healthy banana plants through in vitro culture. Plant Tissue Cult. & Biotech. 35(2): 277-284, 2025 (December)